Adenovirus infection and anti-GBM disease (Goodpasture syndrome): a clinical case - G. E. Lysenko; K. V. Kozlov; E. V. Kryukov; D. M. Shakhmanov; V. G. Arsentiev; R. E. Lahin; A. V. Lyubimov; A. A. Selkina (Журнал инфектологии, 2025)
Goodpasture’s syndrome, an autoimmune disease resulting from the appearance of antibodies to the glomerular basement membrane, is a rare and potentially dangerous complication of infectious diseases such as influenza, new coronavirus infection, adenovirus infection. The course may be atypical and manifest as a severe form of viral disease complicated by acute respiratory distress syndrome and sepsis against the background of an accompanying bacterial infection. The necessary diagnostic methods may be unavailable or performed with a significant delay if biological material is sent to third-party organizations. Timely diagnosis and initiation of specific treatment can reduce mortality by almost half. The article presents a clinical case of a patient with Goodpasture syndrome who was at the clinic of infectious diseases S.M. Kirov Military Medical Academy with acute respiratory viral infection complicated by polysegmental pneumonia.